IMPACT OF MINING INDUSTRY ON THE ENVIRONMENT OF UDAIPUR CITY-A CASE STUDY OF JHAMARKOTRA MINES - 1. Dr. Bhavna Sharma , 2. Dr. Shagufta Saify (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Rajasthan is referred to as a mineral wonderland. Minerals come in a wide variety in Rajasthan. More than 81 different mineral species are available in the state and 52 of which are mined for market purposes. Many companies use minerals as raw materials for production. The state is the leader in the production of important minerals like lead zinc, Gypsum, Wollastonite, Calcite, Ochre, Silver, and Rock Phosphate. The mining sector not only sustains thousands of jobs but also supplies raw materials, minerals and metals that are vital to our economy. They lay the groundwork for advancements in engineering, innovation, and modern living. In essence, mining is a development activity but this industry destroys the environment for economic gain. Therefore, mining operations always result in habitat degradation, biodiversity erosion and deforestation. Environmental pollution is produced in large quantities as a result of the mining and processing of ores and minerals. The studied area Jhamarkotra mine is situated 25 kilometers from Udaipur city. It contains the richest resources of phosphorite ore (rock phosphate) in India. The mine has been in operation for the past few years. Jhamarkotra plays an important role by contributing 98% of the rock phosphate production of India. This research paper is about the effect of the Jhamarkotra mines on the environment of the Udaipur district. It is true that this mine is bliss for the Rajasthan economy but it became the curse for the environment.